2005
DOI: 10.1086/426754
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Photometry of NGC 6791

Abstract: We present deep JHK photometry of the old and metal-rich open cluster NGC 6791. The photometry reaches below the main sequence turn-off to K = 16.5 mag. We combine our photometry with that from Stetson, Bruntt, & Grundahl (2003) to provide color-magnitude diagrams showing K vs. J-K, K vs. V-K, and V vs. V-K. We study the slope of the red giant branch in the infrared, but find that it is not a useful metallicity indicator for the cluster, nor any metal-rich cluster that lacks a well-populated red giant branch, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 47 publications
6
81
0
Order By: Relevance
“…Because of this, the dominant effect is an overall shift in colour while the shape of the isochrones in the CMDs change very little, except at cooler effective temperatures, where uncertainties in e.g. surface boundary conditions (VandenBerg et al 2008), TiO molecular lines (Garnavich et al 1994;Carney et al 2005), and helium content (Girardi et al 2007) makes the interpretation difficult. It is therefore very problematic to use only the CMD to determine cluster parameters from an overall best fit isochrone.…”
Section: Heavy Element Diffusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this, the dominant effect is an overall shift in colour while the shape of the isochrones in the CMDs change very little, except at cooler effective temperatures, where uncertainties in e.g. surface boundary conditions (VandenBerg et al 2008), TiO molecular lines (Garnavich et al 1994;Carney et al 2005), and helium content (Girardi et al 2007) makes the interpretation difficult. It is therefore very problematic to use only the CMD to determine cluster parameters from an overall best fit isochrone.…”
Section: Heavy Element Diffusionmentioning
confidence: 99%
“…They concluded that the star could be either a BSS or a BHB star, but for unknown reason the latter option was the only one which was noted in most later papers which cited their result (e.g. Origlia et al 2006;Carretta et al 2007;Carraro et al 2006;Carney et al 2005;Gratton et al 2006;Boesgaard et al 2009; mentioning just a few). We performed a new spectroscopic analysis of the spectrum obtained by Peterson & Green (1998).…”
Section: Reclassification Of Suspected Blue Horizontal Branch Starsmentioning
confidence: 99%
“…Exactly how high the age must be has been one of the unresolved ongoing controversies regarding the cluster and a driving force behind the need for improved cluster parameters of reddening and metallicity. Among the more recent derivations of key cluster parameters, the reader is referred to Stetson et al (2003), Carney et al (2005), Carraro et al (2006), Origlia et al (2006), Gratton et al (2006), and the many citations therein addressing these long-standing questions.…”
Section: Comparison To Previous Determinations: Reddening and Metallimentioning
confidence: 99%
“…This assumption was repeated or derived for a variety of attempts over the next 20 years, resulting in estimates ranging from E(B À V ) ¼ 0:10 from DDO photometry (Janes 1984) to 0.13 ( Harris &Canterna 1981) and0.20 (Anthony-Twarog &Twarog 1985) from photoelectric UBV data. Although Montgomery et al (1994) adopted the more traditional approach of using UBV color-color diagrams to obtain E(B À V ) ¼ 0:10, over the last 20 years examination of the cluster parameters has been dominated by comparisons to theoretical isochrones and isochrone morphology, either assuming a value for the reddening or adjusting the reddening and metallicity to optimize the match to various CMD and color-color diagrams (Kaluzny 1990;Demarque et al 1992Demarque et al , 2004Meynet et al 1993;Carraro et al , 2006Garnavich et al 1994;Tripicco et al 1995;Kaluzny & Rucinski 1995;Chaboyer et al 1999;Stetson et al 2003;Carney et al 2005). Within this list of citations, prior to the investigation by Chaboyer et al (1999) the adopted and /or derived reddening estimates ranged between E(B À V ) ¼ 0:15 and 0.24, with an average value of 0.20, while the assumed metallicity went between ½Fe/ H ¼ 0:00 and 0.44.…”
Section: Comparison To Previous Determinations: Reddening and Metallimentioning
confidence: 99%
See 1 more Smart Citation